Response policies and strategies for intensification processes of land degradation and desertification in the Republic of Moldova - Tamara Leah (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
Soil, the main means of production in agriculture of Moldova suffered a progressive deterioration in the last 20-30 years due to a intensive operations without adequate investment to preserve and improve its natural properties. Intensive exploitation led to changes in chemical composition (dehumification, alkalinization, salinization) and structure (compaction) and degradation through erosion, pollution, landslides etc. It was estimated a loss of agricultural potential of the soil to 40% due to these direct negative effects of soil degradation. Policy analysis and response strategies showed that the state support of agriculture is very limited. There is no single source of information, containing reports on the amounts (internal and external) have been allocated, the distribution thereof and the name of the projects implemented or under implementation. Evaluation and monitoring of donor funded projects is made in several stages. In this process not involved beneficiaries and the results are made public only in some cases, depending on the scope of the project. To overcome the problems caused by land degradation is required structural agricultural policy, to ensure better use of land.
Keywords: 330; agriculture; degradation; policies; soil; strategies